Synthesis and biological evaluation of new hydrazide-Schiff bases - Asif Husain; Munendra M. Varshney; Versha Parcha; Aftab Ahmad; Shah Alam Khan (Bangladesh Pharmacological Society, 2015)
A new series of N-({5-(substituted aryl)-furan-2-yl}-methylidene)-hydrazides were synthesized with a new class of Schiff bases derived from the reaction of substituted phenyl-1-ketohydrazide 2 or 2-(4-chloro-3-methylaryloxy) acetohydrazide 3 with different 5-(substituted aryl)-2-furfuraldehyde (1a-k) to yield substituted N-({5-(substituted aryl)-furan-2-yl}-methylidene)-hydrazides-Schiff bases (4a-f, 4g-k). The title compounds were subjected to in vitro antibacterial screening against Gram positive bacterial strains- S. aureus, B. cereus, E. faecalis and S. epidermidis, and Gram negative bacteria strains- E. coli, S. typhi, S. dysenteriae  and K. pneumoniae. The synthesized Schiff bases were also evaluated for their anthelmintic activity against two species of earthworms (Pheritima posthuma and Perionyx excavates). Some compounds have shown promising antibacterial and anthelmintic activities.